Conflict, decentralisation and local governance in Colombia, 1974-2004 (2006)
The objective of this paper is to determine the variables that explain the geographical expansion and armed activity of Colombian irregular groups since the mid seventies, taking into account the role of the political, fiscal and budgetary decentralization and its effects over local governance. This period of Colombian history (1974-2004) has been graved by strong economic, social and institutional changes that have deepened particularly since the decentralization process of the mid eighties. In fact, this paper states that decentralization process transformed the conflict into a dispute over the local power, intensifying the use of violence in order to appropriate part of the public goods and resources, interfere the political process and consolidate the group's territorial control. The analysis of the illegal group's early activity (1974-1982) shows that the use of violence is explained by grievances such as poverty or inequality. However, subsequent years reveal deep changes in the illegal group's strategic procedures in which the decentralization process have given them incentives to control the local governments by using violence (greed). The results demonstrate a strong and significant relationship between the intensification of the armed conflict and the greater political, budgetary and fiscal autonomy of local governments. In fact, the presence of local resources such as royalties and taxes triggers violence against politicians being more intense in the municipalities where the actions of the illegal groups are higher.